Investigation of the Anti-Lung Cancer Mechanisms of Taraxacum officinale Based on Network Pharmacology and Multidimensional Experimental Validation - Jianing Liu; Hailing Yang; Ran Liu; Dongjin Sun; Yongbao Liu; Jing Lu; Jinbiao Liu; Junrui Lu (Pharmaceuticals)
Background:Taraxacum officinale(commonly known as dandelion) is a medicinal and edible plant, with the entire plant being used for therapeutic purposes. Studies have demonstrated that dandelion exhibits inhibitory effects against various types of cancer. However, research on its potential for lung cancer (LC) treatment is limited, and the specific compounds responsible for its anticancer effects, as well as the underlying mechanisms, remain unclear. Methods: This study aimed to elucidate the underlying pharmacological mechanisms by which dandelion exerts therapeutic effects against LC. Initially, active compounds of dandelion and their corresponding targets were retrieved from public databases. Subsequently, network pharmacology approaches were applied to identify LC-associated disease targets. By integrating drug-specific targets and disease-related targets, a comprehensive dandelion–lung cancer interaction network was established. Protein–protein interaction (PPI) analyses and functional enrichment studies were further performed to uncover potential molecular mechanisms. Additionally, molecular docking and molecular dynamics (MD) simulations were conducted to evaluate binding interactions between critical active constituents and core targets. To experimentally validate these findings, in vitro cellular assays combined with scanning electron microscopy (SEM) were employed to investigate the anticancer effects of taraxasterol, a key bioactive sterol compound isolated from dandelion, on LC cells. Results: Our analyses identified 58 active compounds in dandelion linked to 614 potential targets, of which 228 targets were associated with LC. The PPI network highlighted 16 core targets, notably TP53, CASP3 and EGFR. Functional enrichment analysis suggested that dandelion might exert its anticancer effects by modulating the tumor microenvironment through the regulation of these critical targets. Molecular docking results demonstrated stable binding interactions between major active compounds and the identified core targets. Furthermore, the anticancer activity of taraxasterol was experimentally validated through in vitro assays and SEM-based morphological assessments, confirming its inhibitory effects on A549 lung cancer cells. Conclusions: Collectively, our findings reveal a multi-targeted therapeutic mechanism of dandelion against LC and support its potential development as a novel natural candidate for lung cancer treatment.